Delayed re-epithelialization in periostin-deficient mice during cutaneous wound healing. - Takashi Nishiyama; Isao Kii; Takeshi G Kashima; Yoshinao Kikuchi; Atsushi Ohazama; Masashi Shimazaki; Masashi Fukayama; Akira Kudo (PLoS ONE, 2011)
BACKGROUND: Matricellular proteins, including periostin, are important for tissue regeneration. METHODS AND FINDINGS: Presently we investigated the function of periostin in cutaneous wound healing by using periostin-deficient ⁻/⁻ mice. Periostin mRNA was expressed in both the epidermis and hair follicles, and periostin protein was located at the basement membrane in the hair follicles together with fibronectin and laminin γ2. Periostin was associated with laminin γ2, and this association enhanced the proteolytic cleavage of the laminin γ2 long form to produce its short form. To address the role of periostin in wound healing, we employed a wound healing model using WT and periostin⁻/⁻ mice and the scratch wound assay in vitro. We found that the wound closure was delayed in the periostin⁻/⁻ mice coupled with a delay in re-epithelialization and with reduced proliferation of keratinocytes. Furthermore, keratinocyte proliferation was enhanced in periostin-overexpressing HaCaT cells along with up-regulation of phosphorylated NF-κB. CONCLUSION: These results indicate that periostin was essential for keratinocyte proliferation for re-epithelialization during cutaneous wound healing.